Business Strategy in Improving the Quality of Productive Credit Distribution at PT. Bank Negara Indonesia (Persero), Tbk. Parepare’s Main Branch Office - Made Bani Kanti Nadi; Nurdin Brasit; Musran Munizu (Hasanuddin Journal of Business Strategy, 2020)
This study aims to analyze the strengths, weaknesses, opportunities, and threats in the Swot analysis, to analyze the positioning with the Swot analysis, as well as to analyze alternative business strategies used by PT. Bank Negara Indonesia. Main Branch Office of Parepare in improving the quality of productive credit distribution. To implement these objectives, data collection techniques are used through observation, questionnaires, and documentation, using descriptive analysis methods, SWOT analysis, IFE, and EFE matrices, External Strategy Factor Analysis (EFAS), Internal Strategy Factor Analysis (IFAS), Grand Strategy Matrix, Tows or SWOT Matrix, Space Matrix, Analysis (QSPM). The results found that the position of PT. BNI (Persero), Tbk. Prepare's Main Branch Office is a position for aggressive growth. Where the growth strategy shows that strengths and opportunities are greater when compared to weaknesses and threats so that the appropriate strategy is used in the growth strategy. BNI strategies are suitable for use by PT. BNI (Persero), Tbk. Prepare's Main Branch Office in improving the quality of productive lending is a market penetration strategy